Efektifitas Kombinasi Terapi Genggam Jari Dan Benson Therapy Terhadap Tekanan Darah - Farida, Denis; Zulkarnain, Octo; Jayadi, Alpian (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2025)
Background: Hypertension or high blood pressure is a condition when blood pressure is consistently above normal values, namely systolic pressure ≥140 mmHg and/or diastolic ≥90 mmHg based on two different measurements. Hypertension can cause various serious complications if not treated properly. Non-pharmacological therapies such as finger grip therapy and Benson are relaxation techniques that are believed to help lower blood pressure naturally. Aim: To determine the effectiveness of the combination of Handheld Jadi and Benson therapy on blood pressure. Method: This study used a Quasi Experiment with a two-group pretest-posttest design. The sample of this study consisted of 46 elderly people who were divided into two treatment groups who received finger grip therapy and Benson therapy, and a control group who did not receive any therapy but received leaflets. Blood pressure was measured before and after treatment using a Sphygmomanometer. Data were analyzed using the Spearman Rho test. Results: The results of the Pearson correlation test with an error rate (α) = 0.05, obtained a p value = 0.000. This means that the combination of finger grip with Benson therapy is effective in lowering blood pressure. Conclusion: The combination of finger grip therapy and Benson therapy has been proven to be effective in lowering blood pressure in the elderly. This therapy can be an alternative to non-pharmacological interventions in the management of hypertension in the elderly. Keywords: Hypertension, Finger Grip Therapy, Benson Therapy, Blood Pressure